Pseudo-orbital SO(6) symmetry for pf-shell nuclei (2006)
ABSTRACT: This work studies the pseudo-orbital SO(6) symmetry for the first half of the {2${\rm p}_{\frac{1}{2}}$}{2${\rm p}_{\frac{3}{2}}$}{1${\rm f}_{\frac{5}{2}}$} shell (denoted as the pf-shell). The spectra and beta decay are calculated for nuclei Ni, Cu and Zn with A=58, and the comparison to experiment prefers the \mbox{$\widetilde{\rm SO}(6)$} limit to the \mbox{$\widetilde{\rm SU}(3)$} one. In the calculation of beta decay two types of transformations are employed and the results seem confirm the adequacy of p-helicity transformation.